Continuous thermosalinograph oceanography along RV SONNE cruise track SO298 - Michael Schlundt; Eric Pieter Achterberg; Gerd Krahmann (PANGAEA, 2024)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after ~12 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. Temperature and salinity were calibrated against CTD data from 4 m depth. For details to all processing steps see Data Processing Report.